Clinical and epidemiological characteristics of outbreaks of acute intestinal diarrheal infections - A. V. Semena; V. V. Malyshev; U. P. Finogeev; I. O. Myasnikov; D. A. Makarov (Журнал инфектологии)
Group carried out epidemiological investigation of the incidence of acute intestinal infections of unknown etiology. Analysis of long-term dynamics of the incidence of acute enteric infections, the population of the city of Rybinsk in 2002 – 2006 he was shown on the epidemiological significance of these infections on the analyzed area. Specific factors of transmission of enteric pathogens on the basis of analysis of existing materials have not been established, but the analysis of risk factors can be said about the dominance of food factor in the transmission of the epidemic process of acute intestinal infections. In order to identify the etiology of acute intestinal infections should be more widely applied in practice techniques for the detection of viral agents in epidemiological investigations.